An emotional roller coaster - family members' experiences of being a caregiver throughout a cancer trajectory. Issue 1 (31st December 2022) - Solberg, Monica; Berg, Geir Vegard; Andreassen, Hege Kristin
ABSTRACT: Purpose: To explore family members' experiences of caregiving throughout a cancer trajectory from diagnosis until around one year after chemotherapy and radiation treatment ended. Method: We conducted a longitudinal qualitative study using in-depth interviews with 13 family members at one to three points of time: before, during, and after treatment. To analyse the interviews, we leaned on Braun and Clark procedure for thematic analysis. Result: The analysis revealed three themes in family members' experiences of being a caregiver to a cancer patient throughout a cancer trajectory. These were: (1) From the time of diagnosis—overwhelming and uncertain; (2) During and after treatment—invisible and not involved; (3) Throughout the cancer trajectory—an emotional roller coaster. Conclusion: The results indicated that the family members felt invisible and not involved and they experienced being a caregiver throughout the cancer trajectory as an emotional roller coaster. Our empirical findings thus indicate that in cancer care, family perspectives are yet to be implemented in daily practice. This is in contrast to explicit goals in current health policies underlining support and involvement of family members as a core aspect in cancer care.